Influence of Silver Loaded Antibacterial Agent on Knitted and Nonwoven Fabrics and Some Fabric Properties. Issue 1 (March 2016) - Erdem, Ramazan; Rajendran, Subbiyan
The antibacterial effect of silver on knitted and nonwoven structures has been investigated. Three types of interlocked knitted fabrics (100% polyester, 100% viscose and 50%/50% polyester/viscose) were scoured and treated with silver ions by pad-dry-cure method. A nonwoven fabric (100% bleached cotton) was also treated with silver ions by using a spray technique. Physical and tensile properties of the treated fabrics were analyzed and compared with those of corresponding untreated ones. Results indicate that scouring process and antimicrobial treatment influenced the physical properties and antimicrobial effectiveness of the fabrics. An increase in tensile strength of 100% polyester and 100% viscose is observed after the antimicrobial treatment. The absorbency of all the treated knitted fabrics is decreased but it is substantially increased in the case of nonwoven fabrics. Antimicrobial activity of the treated fabrics was tested against Gram-positive bacterium Staphylococcus aureus . The results show that the treated nonwoven and blended (50%/50% polyester/viscose) knitted fabrics registered highest antimicrobial effect.